2006
DOI: 10.1074/jbc.m600353200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Lipase-linked Cell Membrane Receptor for Pigment Epithelium-derived Factor

Abstract: Pigment epithelium-derived factor (PEDF) is an extracellular multifunctional protein belonging to the serpin superfamily with demonstrable neurotrophic, gliastatic, neuronotrophic, antiangiogenic, and antitumorigenic properties. We have previously provided biochemical evidence for high affinity PEDFbinding sites and proteins in plasma membranes of retina, retinoblastoma, and CNS cells. This study was designed to reveal a receptor involved in the biological activities of PEDF. Using a yeast two-hybrid screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
295
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 257 publications
(311 citation statements)
references
References 65 publications
7
295
1
Order By: Relevance
“…The structure of the exons of PNPLA2 reflects the proposed domain structure of the protein with three endodomains (L1, L3, and L5) and two ectodomains (L2 and L4) (35). Immunoreactivity of non-permeabilized cells, FACS, antibody capture experiments using antibodies to peptides from intracellular L3 and extracellular L4 domains, and cell surface biotinylation experiments agree with the predicted PEDF-R topology and show that PEDF-R is one of the proteins labeled at the surface of ARPE-19 cells (26). The amino acid sequence reveals a phospholipase A 2 (PLA 2 ) domain toward its amino end.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…The structure of the exons of PNPLA2 reflects the proposed domain structure of the protein with three endodomains (L1, L3, and L5) and two ectodomains (L2 and L4) (35). Immunoreactivity of non-permeabilized cells, FACS, antibody capture experiments using antibodies to peptides from intracellular L3 and extracellular L4 domains, and cell surface biotinylation experiments agree with the predicted PEDF-R topology and show that PEDF-R is one of the proteins labeled at the surface of ARPE-19 cells (26). The amino acid sequence reveals a phospholipase A 2 (PLA 2 ) domain toward its amino end.…”
supporting
confidence: 56%
“…The amino acid sequence reveals a phospholipase A 2 (PLA 2 ) domain toward its amino end. Indeed, PEDF-R exhibits PLA 2 , triglyceride lipase, and acylglycerol transacylase activities (26,34). Moreover, we have shown that PEDF stimulates the PLA 2 activity of the PEDF-R enzyme, resulting in the release of fatty acids from phospholipids (26,35).…”
mentioning
confidence: 91%
See 3 more Smart Citations